2019
DOI: 10.1007/s00787-019-01391-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to parental pre-treatment motivation in outpatient child and adolescent mental health care

Abstract: The aim of this study was to investigate the relation between a variety of child, parent, family and environmental factors and pre-treatment motivation of parents of children and adolescents newly referred to a mental health care clinic in The Netherlands. Data were collected of 521 parents most involved in the upbringing of the child (443 mothers and 78 fathers; Dutch origin 97.1%) of 207 girls and 314 boys (age M = 10.2, range 1-18 years). Treatment motivation was measured by the Parent Motivation Inventory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
(70 reference statements)
2
6
1
Order By: Relevance
“…However, the correlation between lower parental treatment motivation and NSSI of longer duration in children could also be due to a selection effect as a result of the study design (i.e., because children who were already in treatment were excluded from the study). Contrary to the results of this present study (that parents showed less readiness for change when their children engaged in NSSI for a longer duration), another study [34] found that the severity of internalizing problems, followed by externalizing problems, was the strongest predictor for higher parental treatment motivation. The difference to our study could be due to the fact that the aforementioned study used an outpatient sample in a child and adolescent psychiatric service.…”
Section: Discussion/conclusioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the correlation between lower parental treatment motivation and NSSI of longer duration in children could also be due to a selection effect as a result of the study design (i.e., because children who were already in treatment were excluded from the study). Contrary to the results of this present study (that parents showed less readiness for change when their children engaged in NSSI for a longer duration), another study [34] found that the severity of internalizing problems, followed by externalizing problems, was the strongest predictor for higher parental treatment motivation. The difference to our study could be due to the fact that the aforementioned study used an outpatient sample in a child and adolescent psychiatric service.…”
Section: Discussion/conclusioncontrasting
confidence: 99%
“…The proportion of mothers filling in the questionnaires and thus acting as accompanying persons for the children was about 80% at T2. This proportion of mothers is found to be similar or even higher in other studies [31, 34, 55]. The GSI, an indicator of psychological distress, was assessed and we found higher GSI values in girls than in boys.…”
Section: Discussion/conclusionsupporting
confidence: 90%
See 2 more Smart Citations
“…Participants were 317 parents (97% Dutch origin) with a child aged below 18 years referred to one of two child and adolescent psychiatry outpatient clinics with several locations in the Northern or Eastern part of the Netherlands including both rural and urban areas, covering a large catchment area. The current sample concerns the baseline and third wave (about one year later) of a larger three-wave study aimed at collecting data on a large number of child, family, and social-environmental factors that could influence outpatient treatment of children and adolescents referred to the clinic [37]. Children had to be newly referred (i.e., first referral to the respective mental healthcare clinic) to be eligible to participate in the study.…”
Section: Study Sample and Designmentioning
confidence: 99%